Sustainable Development and Institutionalization of Extension: Impacts of a Virtual Extension Project in Chemistry During COVID-19 (Research, Society and Development, 2022)
The COVID-19 pandemic crisis impacted on how university extension is done. Extension plays an essential role in chemistry. In Brazil, a new regulatory framework for university extension must be implemented. However, educational institutions are facing difficulties to institutionalize extension. Consequently, there is a lack of papers describing engagements of the university community. In this perspective, this report aims to describe a virtual university extension project with the Sustainable Development Goals (SDGs). The method used is qualitative and participative. The methodology used was the case report, with qualitative and participatory analysis. The target audience covered the internal communities - students and employees of the institution - and external - undergraduates from other institutions, high school students, guest speakers, among others enrolled. Every activity was developed with digital resources and social medias, as WhatsApp. In this way, the project can be reformulated by other universities. Results indicated that Digital Information and Communication Technologies (DICTs) potentialized an accessible and inclusive participation of the community in environmental knowledge. The development of this project proved to be a multidisciplinary strategy for including sustainable development extension in a chemistry course curriculum. In conclusion, a creative strategy to attend the new regulatory framework for university extension in Brazil is offered.